The Role Of Digital Marketing Content Tools In Building Public Trust In Kupang City To Online Shopping - Kamuri, Klaasvakumok Jehezkielomi; Anabuni, Andrias Umbu Tuku; Riwu, Yonas Ferdinand; Manongga, Irience Rachel Agatha (PT Keberlanjutan Strategis Indonesia, 2023)
To build consumer trust through online sales, business people can utilize digital marketing content tools, which are a determining factor in building consumer trust. This research aims to describe how the role of digital marketing content tools builds trust in a person to do online shopping. The object of this research is the people of Kupang City who are active in doing online shopping activities, which are studied using qualitative descriptive methods. The results show that in creating consumer trust for online shopping, social media acts as a facilitator through the right aspects, namely, relationship, communication, content, and connection. Search Engine Optimization (SEO) acts as a credible information center because it is able to map the profile of marketers and their products based on other users' experiences and ratings of marketers' reputation, product quality, and service quality. Pay Per Click (PPC) acts as executive sales and video marketing through its visualization power, acting as a source of information as well as an effective teaching tool to illustrate how the product should be used.